Pengaruh Literasi Keuangan terhadap Pengelolaan Keuangan melalui Locus of Control dan Self-Efficacy - Cindy Pramithasari; Purwo Adi Wibowo (Penerbit Goodwood, 2025)
Purpose: This study aims to reveal the most important things among financial literacy, financial locus of control, and financial self-efficacy towards personal financial management. Methodology: The population consists of 52 security guards working at PT Berkah Mitra Abadi. Sampling method with a census and data collection using a questionnaire. The data obtained were then processed using the partial least square (PLS) method with SmartPLS 3.2.9 software. Results: Financial literacy has a significant positive effect on personal financial management, financial locus of control, and financial self-efficacy. The financial self-efficacy variable can act as a mediating variable for personal financial management (because financial self-efficacy has a significant positive effect on personal financial management), whereas financial locus of control cannot act as a mediating variable (because financial locus of control has no effect on personal financial management). Conclusion: Financial literacy has a significant positive effect on personal financial management, financial locus of control and financial self-efficacy in security guards. Limitations: This research only takes the unit of analysis of security guards at PT Berkah Mitra Abadi Semarang employees, so it cannot represent other professions. Contribution: The research results provide an overview of personal financial management in the security profession.